Formulasi Kebijakan Kolaborasi Pengelolaan Pariwisata di Kabupaten Merauke - Ransta L Lekatompessy; Edoardus E. Maturbongs; Fiqih, Fiqih; Puspita Wulan Sari (SOCIETAS, 2023)
Policy Formulation is a process of formulating policies or strategies to achieve the desired goals. There is no Regency Tourism Development Management Agency that should be regulated in the Regent's Regulation, so the government is expected to immediately form a tourism management body so that the forum together with the Tourism Office always synergizes in the process of planning, organizing, supervising, and controlling activities related to tourism, including promotion, development of tourism products, and conservation environment and culture. The method used in this research is descriptive qualitative research, with data collection techniques by observation, in-depth interviews(depth interview), Focus Group Discussion (FGD), and documentation study. The results of this study, namely the formulation of collaborative tourism management policies in Merauke Regency involve five parties, namely local government, academics, communities, tourism business actors, and the mass media. The Pentahelix collaboration is very important to create synergy and cooperation in tourism management which is accommodated by the Regency Tourism Management Board, the formation of a tourism management body will allow tourism development to be more directed and integrated, to optimize the resulting economic, social, and environmental benefits.